2019
DOI: 10.2460/ajvr.80.12.1089
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intramuscular administration of alfaxalone-ketamine-dexmedetomidine and alfaxalone-butorphanol-midazolam in naked mole-rats (Heterocephalus glaber)

Abstract: OBJECTIVE To compare anesthetic effects of alfaxalone-ketamine-dexmedetomidine (AKD) and alfaxalone-butorphanol-midazolam (ABM) in naked mole-rats (Heterocephalus glaber). ANIMALS 20 naked mole-rats. PROCEDURES Naked mole-rats received AKD (alfaxalone, 2 mg/kg; ketamine, 20 mg/kg; and dexmedetomidine, 0.02 mg/kg; n = 10) or ABM (alfaxalone, 2 mg/kg; butorphanol, 2 mg/kg; and midazolam, 1 mg/kg; 9) IM; 1 animal was removed from the study. Atipamezole (I mg/kg) and flumazenil (0.1 mg/kg) were administered 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The smooth induction quality observed in this study is similar to what has been observed in naked mole rats (Heterocephalus glaber) and fivestriped palm squirrels (Funambulus pennantii) receiving various combinations of alfaxalone with ketamine, dexmedetomidine, butorphanol, or midazolam. [12][13][14][15] In contrast, chinchillas (Chinchilla lanigera) anesthetized with alfaxalone-butorphanol experienced rolling, twitching, and tremors throughout induction of anesthesia, mice given alfaxalone or alfaxalonexylazine experienced erratic jumping and limb jerking during induction, and rats frequently twitched during recovery when given alfaxalone intraperitoneally. 13,18,21,32 This could perhaps be attributed to the use of significantly higher alfaxalone doses in rats and mice; however, the chinchillas in the aforementioned study received comparable alfaxalone doses to the dose evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The smooth induction quality observed in this study is similar to what has been observed in naked mole rats (Heterocephalus glaber) and fivestriped palm squirrels (Funambulus pennantii) receiving various combinations of alfaxalone with ketamine, dexmedetomidine, butorphanol, or midazolam. [12][13][14][15] In contrast, chinchillas (Chinchilla lanigera) anesthetized with alfaxalone-butorphanol experienced rolling, twitching, and tremors throughout induction of anesthesia, mice given alfaxalone or alfaxalonexylazine experienced erratic jumping and limb jerking during induction, and rats frequently twitched during recovery when given alfaxalone intraperitoneally. 13,18,21,32 This could perhaps be attributed to the use of significantly higher alfaxalone doses in rats and mice; however, the chinchillas in the aforementioned study received comparable alfaxalone doses to the dose evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery quality for both studied protocols was smooth with no obvious adverse events, similar to the observed recovery quality of naked mole rats after receiving alfaxalone based anesthetic protocols. 14,15 Prior studies 18,21,32 evaluating alfaxalone in rats and mice or alfaxalone combined with xylazine in mice observed erratic jumping behavior, intense facial scratching, limb jerking, and facial twitching during the recovery period. Five-striped palm squirrels experienced twitching, tail lifting, and vocalization throughout recovery after receiving Body temperature was significantly different between protocols (P < .001), over time (P < .001) (Figure 4), but not with weight (P = .55).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations